2009
DOI: 10.1007/s10295-009-0593-0
|View full text |Cite
|
Sign up to set email alerts
|

Start-up and inhibition analysis of the Anammox process seeded with anaerobic granular sludge

Abstract: The longer start-up period of the Anammox process is due to the very low cellular yield and growth rates of Anammox bacteria. Nitrite inhibition is considered to be the key factor in the instability of the Anammox process during the operation. However, little attention was paid to the inhibitory effect of pH and free ammonia. This paper presents start-up and inhibition analysis of an Anammox biofilm reactor seeded with anaerobic granular sludge. Results showed that the start-up period could be divided into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(48 citation statements)
references
References 27 publications
3
44
1
Order By: Relevance
“…Just around 10 days were taken to start up anammox successfully in R1, indicating that the anammox bacteria entrapped in the PVA-SA gel beads could be activated rapidly and the anammox process could be triggered rapidly using whole cell entrapment of anammox biomass. In contrast, the start-up of the anammox reactor using common activated sludge as seed usually requires a much longer period of around 90-120 d due to the slow growth rate and low biomass yield as well as stringent metabolic conditions of anammox bacteria [4,17,[20][21], which is thus a large obstacle for its application. The removal efficiencies of nitrite and ammonium decreased sharply by half when the HRT was reduced from 24 h to 12 h on day 26.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Just around 10 days were taken to start up anammox successfully in R1, indicating that the anammox bacteria entrapped in the PVA-SA gel beads could be activated rapidly and the anammox process could be triggered rapidly using whole cell entrapment of anammox biomass. In contrast, the start-up of the anammox reactor using common activated sludge as seed usually requires a much longer period of around 90-120 d due to the slow growth rate and low biomass yield as well as stringent metabolic conditions of anammox bacteria [4,17,[20][21], which is thus a large obstacle for its application. The removal efficiencies of nitrite and ammonium decreased sharply by half when the HRT was reduced from 24 h to 12 h on day 26.…”
Section: Resultsmentioning
confidence: 99%
“…3b). Acidity can be consumed in anammox reaction, with the pH level in the reactor elevated [4,21]. The effluent pH value increased gradually after the experiment began, and was clearly higher than that of the influent -especially in operational phase 2, indicating intense anammox activity in the reactor.…”
Section: Stoichiometric Characteristics Of the Immobilized Anammox Rementioning
confidence: 99%
“…This removal could be attributed to the prevalence of denitrification process. The organic released from cell lysis can be used as an electron donor by heterotrophic denitrifying bacterial communities for denitrification process [24]. The sludge lysis phase lasted for only one week.…”
Section: The Start-up Of Anammox Bacteria In Mabr Reactor (Days 1-150)mentioning
confidence: 99%
“…Based on the above results, the MABR reactor exhibited excellent performance for the start-up of Anammox process within a period of 35 days using activated sludge (mixed culture bacteria, 41.6 g MLSS/L and 19.1 g MLVSS/L) as inoculum. Tang, Zheng, et al [24] demonstrated that an Anammox reactor was successfully started up on day 73. Tsushima et al observed Anammox reactions after a 55-day the start-up process [26].…”
Section: The Start-up Of Anammox Bacteria In Mabr Reactor (Days 1-150)mentioning
confidence: 99%
“…Application of ANAMMOX process or coupling partial nitrification with ANAMMOX seemed promising. It could result in 60% savings in O 2 generation, 100% savings of external carbon source addition, less sludge production and CO 2 emission, with a total reduction in treatment cost by 90% [14,[24][25][26].…”
Section: Reactor Configurationsmentioning
confidence: 99%